(untitled) (Computer systems and information technologies, 2022)
The development of science and education is now exposed to a huge impact of such civilizational challenges as: climate change, which is due to global warming, excessive and unjustified consumption of material goods, environmental pollution; pandemic COVID 19 and the emergence of new diseases and as the quintessence of human irresponsibility and callousness, activation on a global scale, and in Ukraine in particular, hybrid wars against universal values. This situation causes a massive shift to a remote format of the organization of scientific and educational (research) process, including the training of scientific personnel in higher education institutions and research institutes, using certain networked information and computer technologies and systems. Therefore, the purpose of the study, the current results of which are presented in the article, is to study the problems of applying the methodology of building information-analytical systems (hereinafter – IAS), in particular digital IAS, and to substantiate the basis and highlight in this context the main aspects of creating an ontological model of scientific personnel training (hereinafter – SPT) system as part of a single information space of scientific education. The author raises the problem of the need to apply transdisciplinary methodology of building digital information-analytical system of scientific personnel training in higher education institutions (hereinafter – HEI) and research institutes (hereinafter – RI) of Ukraine in a distance. Particular attention is paid to the ontological modeling of IAS components of the relevant organization of effective scientific and educational (research) process. Also basic definitions of the ontological approach to the training of scientific personnel disclosed. The article considers certain requirements for the design and functioning of intelligent educational systems and programs that provide adaptive information-analytical support of scientific personnel training on the basis of transdisciplinary, system, competence and ontological approaches. The analysis of a certain base of sources (researches and publications) is given. Thus, the methodological basis for building a digital information-analytical system in the specified context is presented and certain fragments of its ontological model are proposed. The presented approbation of applied aspects of the author’s research is in the ascertaining stage. Subsequent results of analytical-synthetic and formative stages of the presented doctoral research are passing into the phase of experimental verification and the obtained data will be made public in the following publications of the author.